Palliative chemotherapy for pancreatic adenocarcinoma: a retrospective cohort analysis of efficacy and toxicity of the FOLFIRINOX regimen focusing on the older patient - Berger, Anne Katrin; Haag, Georg Martin; Ehmann, Martin; Jäger, Dirk; Springfeld, Christoph (BMC gastroenterology, 2017)
Pancreatic cancer occurs more frequently in older patients, but these are underrepresented in the phase III clinical studies that established the current treatment standards. This leads to uncertainty regarding the treatment of older patients with potentially toxic but active regimens like FOLFIRINOX.
Gesehen am 25.04.2018